Perlindungan Hukum Nasabah sebagai Syarik dalam Pembiayaan Al Musyarakah di Bank Syariah Mandiri - Bagya Agung Prabowo (Jurnal Hukum IUS QUIA IUSTUM, 2011)
Musyarakah is a profit and loss sharing partnership. In Musyarakah financing, bank and customer contribute capital and skill in a project. The profit and loss will be normally divided based on the contribution. The discussed problem in this research is legal protection for customer in musyarakah financing and the legal status of guaranty and encumbrance in musyarakah financing of Yogyakarta Branch of Bank Syariah Mandiri. This research is a juridical empiric research. The secondary data is obtained by literary study from primary, secondary, and tertiary legal material. The result of this research showed that there must be equality in every transaction in Yogyakarta Branch of Bank Syariah Mandiri, because every financial process contains risk and profit in order to be a bound of trust which guarantees mudharib to find their obligation in the future as stipulated in musyarakah financing agreed before.Key words : Musyarakah, legal protection, equality